(untitled) - The World Bank (Washington, D.C., 2006)
Doing Business in 2006 is the third in a series of annual reports investigating regulations that enhance business activity and those that constrain it. This edition provides analysis on those regulations that help create jobs and those that deter it. New quantitative indicators on business regulations and their enforcement can be compared across 150 countries - from Albania to Zimbabwe - and over time.
Keywords: The World Bank,Economic assistance,Economic development projects,Dự án phát triển kinh tế,Hỗ trợ kinh tế; Economic assistance,Developing countries,Evaluation,Developing countries,Evaluation,Phát triển quốc gia,Đánh giá,Phát triển quốc gia,Đánh giá